Drug-induced peripheral neuropathy. (October 2016) - Green, Sarah; Holton, Andrew
Abstract : Summary: Drug-induced peripheral neuropathy is an important clinical problem. It can cause irreversible symptoms such as pain and numbness that have an enormous impact on ability to function normally and perceived quality of life. This can lead to dose reductions or a requirement to cease treatment with a particular drug. The mechanisms of damage are not always fully understood, but particular drugs such as the cancer chemotherapy agents are well known as identified causes of peripheral neuropathy. Investigative methods are not always satisfactory and the diagnosis is frequently clinical. It is important for clinicians to be aware of the problem so that patients at risk are asked the relevant questions.